Community based integrated wound care: Results of a pilot formative research conducted in Benin and Côte d'Ivoire, West Africa. - Anita Carolle Akpeedje Wadagni; Théodore Ange Kouakou Yao; Gabriel Diez; Flora Houndjrèbo Balle; Aboa Paul Koffi; Paulin Aoulou; Marie-Hélène Zahiri; Parfait Djossou; Yves Thierry Barogui; Henry Assé; Jean-Gabin Houezo; Ghislain Emmanuel Sopoh; et al. (Public Library of Science (PLoS), 2024)
Appropriate treatment of chronic wounds is priority in the management of Neglected Tropical Skin Diseases (NTSDs) and non-communicable diseases. We describe an integrated, community-based wound care pilot project carried out in Benin and Cote d'Ivoire that entailed both outreach education and evidence based wound care training for nurses staffing rural clinics. This research was carried out by a transdisciplinary research. Following the collection of baseline data on wound care at home and in clinics, an innovative pilot project was developed based on a critical assessment of baseline data in three parts: a pragmatic nurse training program; mass community cultural sensitive outreach programs and a mobile consultation. It came out from our investigation that several dangerous homecare and inappropriate wound treatment practices in clinics, gaps in knowledge about Neglected Tropical Skin Diseases (NTSDs), and little health staff communication with patients about appropriate wound care. Nurse training covered 11 modules including general principles of wound management and advice specific to endemic NTSDs. Nurse pre-post training knowledge scores increased substantially. Eight mass community outreach programs were conducted, followed by mobile clinics at which 850 people with skin conditions were screened. Three hundred and three (35.65%) of these people presented with wounds of which 64% were simple, 20% moderate, and 16% severe cases. Patients were followed for ten weeks to assess adherence with wound hygiene messages presented in outreach programs and repeated by nurses during screening. Over 90% of simple and moderate cases were managed appropriately at home and 98% of wounds were healed. Of the 47 cases referred to the health center, 87% came for and adhered to wound care advice. In 90% of cases, wounds healed. This pilot study provides a model for introducing integrated community based wound care in Africa.